Pembelajaran berbasis produksi untuk peningkatan kompetensi membuat gambar kerja teknik mesin siswa SMK - Pardjono Pardjono; Albertus Murdianto (Jurnal Pendidikan Vokasi, 2011)
PRODUCTION-BASED LEARNING TO IMPROVE COMPETENCE IN MAKING MECHANICAL ENGINEERING DRAWINGS OF VOCATIONAL STUDENTSThis study is aimed at improving quality of learning process of Mechanical Drawing by employing Production Based Training to achieve mechanical drafter competency. Consecutively this research will also develop teacher's professionalism in managing learning process of Mechanical Drawing at SMK Sf Mikael.This classroom action research was conducted in SMK St. Mikael Surakarta. Grade XI was assigned to be subject of this research. Two collaborators were assigned to back up and assist the researchers to monitor the effects of action on student competency in mechanical drawing. The changes due to the action are monitored through observation by involving the two collaborators. The collected data was analyzed descriptively. The data analysis resulted in the following findings: (a) production based learning improves students achievement in reaching the minimum mastery criteria on Mechanical Drawing and more specifically improves student competency in producing machining industries standardized of Mechanical Working Drawing, (b) a process of expertise acquition in mechanical working drawing through combination of constructivism learning principles, behaviorism, situated learning and cognitive apprenticeship; (c) the production-based learning increases students' ability behave discipline and attitude toward mechanical drawing, and (d) production based learning was implemented through classroom discussion on the mechanical drawing principles, its implementation on working drawings, integrating knowledge on components stradard as well as production process into working drawing.